If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11z = -33 + 8z Solving 11z = -33 + 8z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-8z' to each side of the equation. 11z + -8z = -33 + 8z + -8z Combine like terms: 11z + -8z = 3z 3z = -33 + 8z + -8z Combine like terms: 8z + -8z = 0 3z = -33 + 0 3z = -33 Divide each side by '3'. z = -11 Simplifying z = -11
| 4t=2t-10 | | C=a+8 | | y=3x^4-6x^2+3 | | =31/2*(1-3)^4 | | 12.31+0.07x=12.81+0.08x | | X+8=4X+3+229 | | x/12-3=5/24 | | -12X+14=-24 | | (-5+3i)(4+7i)= | | 39+-12w=7+-16w | | 180-i=(i-56) | | k-9.5=10 | | 15+5z=10 | | k-9.5=10whatisk | | 1/-12÷2/3 | | 0.7x+3.1=0.6x+1.6 | | tn-1=tn-1+2 | | Y-1=9y-9 | | y+8+15=2 | | 5x+8y=23 | | 2x=5.67 | | 16a=25*64 | | 3.6x-24=2.1x+9 | | c+(c-20)+(c-10)=180 | | z^2+7z=7 | | 2/3*7/20 | | 2(2x-1.8)=5x-3.6 | | 2x(x+7)=(x-1)(x+7) | | 12x-21=63-9x | | 104=-8(-5-2n) | | ln(2x+1)-ln(5x-2)=0 | | 4k-3=17 |